2020
DOI: 10.1101/2020.08.19.256925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism of negative membrane curvature generation by I-BAR domains

Abstract: The membrane sculpting ability of BAR domains has been attributed to the intrinsic curvature of their banana-shaped dimeric structure. However, there is often a mismatch between this intrinsic curvature and the diameter of the membrane tubules generated. For example, I-BAR domains are almost flat but generate much higher membrane curvature. Furthermore, F-BAR and I-BAR domains are quite similar, but the former generates positive curvature and the latter negative curvature. Here, we use implicit-solvent compute… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In vitro studies have shown the SH3 domain of these proteins can directly activate N-WASP-mediated actin polymerization on liposomes with a specific diameter 21,26 . The other BAR proteins, like I-BAR (IRSp53), recruit actin regulatory proteins like VASP, mDia2 and WAVE2 through SH3 domain interaction 27,[60][61][62][63][64][65][66][67] . Our research now clarifies how the SH3 domain contributes to nanoscale N-WASP clustering upon precise curvature sensing by BAR, promoting localized Arp2/3 activation and robust actin nucleation.…”
Section: Curvature Sensor Bar Proteinmentioning
confidence: 99%
“…In vitro studies have shown the SH3 domain of these proteins can directly activate N-WASP-mediated actin polymerization on liposomes with a specific diameter 21,26 . The other BAR proteins, like I-BAR (IRSp53), recruit actin regulatory proteins like VASP, mDia2 and WAVE2 through SH3 domain interaction 27,[60][61][62][63][64][65][66][67] . Our research now clarifies how the SH3 domain contributes to nanoscale N-WASP clustering upon precise curvature sensing by BAR, promoting localized Arp2/3 activation and robust actin nucleation.…”
Section: Curvature Sensor Bar Proteinmentioning
confidence: 99%